Reduced Vitamin K Status as a Potentially Modifiable Risk Factor of Severe Coronavirus Disease 2019. (27th August 2020) - Dofferhoff, Anton S M; Piscaer, Ianthe; Schurgers, Leon J; Visser, Margot P J; van den Ouweland, Jody M W; de Jong, Pim A; Gosens, Reinoud; Hackeng, Tilman M; van Daal, Henny; Lux, Petra; Maassen, Cecile; Karssemeijer, Esther G A; et al.
Abstract: Background: Respiratory failure and thromboembolism are frequent in severe acute respiratory syndrome coronavirus 2–infected patients. Vitamin K activates both hepatic coagulation factors and extrahepatic endothelial anticoagulant protein S, required for thrombosis prevention. In times of vitamin K insufficiency, hepatic procoagulant factors are preferentially activated over extrahepatic proteins. Vitamin K also activates matrix Gla protein (MGP), which protects against pulmonary and vascular elastic fiber damage. We hypothesized that vitamin K may be implicated in coronavirus disease 2019 (COVID-19), linking pulmonary and thromboembolic disease. Methods: A total of 135 hospitalized COVID-19 patients were compared with 184 historic controls. Inactive vitamin K–dependent MGP (desphospho-uncarboxylated [dp-uc] MGP) and prothrombin (PIVKA-II) were measured inversely related to extrahepatic and hepatic vitamin K status, respectively. Desmosine was measured to quantify the rate of elastic fiber degradation. Arterial calcification severity was assessed using computed tomography. Results: dp-ucMGP was elevated in COVID-19 patients compared with controls ( P  < .001), with even higher dp-ucMGP in patients with poor outcomes ( P  < .001). PIVKA-II was normal in 82.1% of patients. dp-ucMGP was correlated with desmosine ( P  < .001) and with coronary artery ( P  = .002) and thoracic aortic ( P  < .001) calcification scores. Conclusions: dp-ucMGP was severely increased in COVID-19 patients, indicating extrahepatic vitamin K insufficiency, which was related to poor outcome; hepatic procoagulant factor II remained unaffected. These data suggest pneumonia-induced extrahepatic vitamin K depletion leading to accelerated elastic fiber damage and thrombosis in severe COVID-19 due to impaired activation of MGP and endothelial protein S, respectively. Abstract : Indirectly quantified extrahepatic vitamin K status is severely reduced in COVID-19. Data suggest pneumonia-induced vitamin K depletion leading to elastic fiber damage and thrombosis due to impaired vitamin K–dependent activation of matrix Gla protein and endothelial protein S, respectively.